Analysis of Malaysian natural rubber price through supply and demand / Muhammad Taufiq Abd Jaza - Abd Jaza, Muhammad Taufiq (Faculty of Plantation and Agrotechnology, 2019)
Natural rubber is grown very nearly in Southeast Asia develop as commodities market in Malaysia. Natural rubber market were imbalanced on demand and supply, therefore its impact on natural rubber price. The aim of study is to determine the most affected factor of natural rubber price of SMR20 in the Malaysia, and to analyse mutual-relation of Malaysian natural rubber price SMR20 with domestic supply and demand. Therefore, the natural rubber price determination model was built. The data provide in this study is secondary data. The time series data of this study is by using the monthly data from year 2016 to 2018. The data provided were gathered from Malaysian Rubber Board, Department of Statistics Malaysia, and Malaysian Rubber Board. It is uses natural rubber price SMR20 as dependent variable, while natural rubber production and consumption, crude oil palm price as independent variable. This study test whether there have long-run equilibrium relationship between the price of natural rubber in Malaysia and a set of explanatory variable that influence it. The Augmented Dickey-Fuller (ADF) reveal that all the series are significant at first difference. The Johansen Co-integration test show that the model were co-intregrating relationship. The vector error correction model (VECM) were conducted in this test. Findings show that at the long run, production have positive significance, while consumption and oil palm price have negative significance on price and a one-way casuality from consumption to price in short-term. All the factors in the natural rubber price equation showed the expected signs which is the price of natural rubber (PSMR20) was significantly related to demand and supply of natural rubber, and price of oil palm. The natural rubber stakeholders should co-operate in planning and setting up appropriate natural rubber policies to balance supply and demand on the world market which would impact natural rubber price stabilization in the future.